Avaliação da atividade antimicrobiana e antibiofilme de pequenos peptídeos catiônicos contra Klebsiella pneumoniae - Ribeiro, Suzana Meira (2014)
Multi-drug resistant Klebsiella pneumoniae that produce the enzyme K. pneumoniae carbapenemase (KPC) are becoming a common cause of infections in health care centers. Furthermore, Klebsiella can develop multicellular biofilms, which lead to elevated adaptive antibiotic resistance. Here, it was described the antimicrobial and anti-biofilm activities of synthetic cationic peptides against K. pneumoniae strains susceptible and carbapenens resistant through in vitro and in vivo assays. By using static microplate assays, it was observed that the concentration of the peptides IDR-1018, DJK-5 and DJK-6 required to prevent biofilm formation by these clinical isolates was below the minimum inhibitory concentration (MIC) of these peptides. Flow cell experiments confirmed the anti-biofilm activity of the peptides against 2 day-old biofilms of different KPC producing isolates and, in some cases, the peptides induced biofilm cell death. Combinations of DJK-6 together with β-lactam antibiotics, including the carbapenem meropenem, also prevented planktonic growth and biofilm formation of KPC producing strain 1825971. Interestingly, the peptide DJK-6 was able to enhance, by at least 16-fold, the ability of meropenem to eradicate pre-formed biofilms formed by this strain. Although, this combination between meropenem, DJK-6 was effective in vitro, any reduction of bacterial load was observed in murine lung model of infection. Similarly, the peptides HHC-10, IDR-1018 e IDR-1002 was effective in vitro, but ineffective in vivo. The results in vivo, using the peptides HHC-10 and IDR-1018 after infection were contrasting (significant reduction or non-reduction of bacterial load) between two models of lung infection. Others approaches using the peptides IDR-1018 prophylactically or the peptide IDR-1002 (effective in inhibit bacterial growth) before the induction of the infection, as a preventive approach or IDR-1002 (peptide that reduced the bacterial counts in vitro) after infection, also was unable to reduce the bacterial load in lungs of mice. Despite ineffective in acute model of lung infection, the use of cationic peptides, such DJK-6, to potentiate the activity of β-lactams including meropenem, represents a promising strategy to prevent biofilm formation or eliminate existent biofilms both in medical devices and in body surfaces.